(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In this article, the opinions of modern enlighteners about the rules of family and family management are discussed. In particular, attention is paid to the socio-philosophical analysis of the stages and directions of family formation in the scientific and educational views of Abdurauf Fitrat, Abdulla Avloni, Mahmudhoja Behbudi. An opinion is expressed about what is the basis for family strength.